Assemblage, adaptation and apps: Smartphones and mobile gaming. - Christensen, Christian; Prax, Patrick (Continuum: Journal of Media & Cultural Studies, 2012)
As scholars such as Goggin (2009a) have noted, the rapid uptake of ‘smartphones’ has reshaped the ways in which software developers, users, and academics consider the interrelationship between mobility, culture, technology hardware, and the Internet. In addition, this uptake has added a significant new layer of encrustations around what we might define as ‘standard’ uses of mobile technologies. Once limited to the playing of pre-loaded (offline) games on mobile handsets, smartphones have allowed for not only mobile interactivity and enhanced visuals, but also the possibility of downloading apps that allow the user to add multiple new dimensions to the gaming experience. These developments are but one more factor in ‘thinking about games as assemblage, wherein many varying actors and unfolding processes make up the site and action’ (Taylor 2009, 332). Taking the theoretical perspectives of adaptation (Goggin 2009a; Farnsworth and Austrin 2010) and assemblage (Taylor 2009; Goggin 2009b) we will discuss three apps linked to the enormously popular World of Warcraft game, and the ways in which these applications both reshape how we might think about and use technology, and how smartphones and mobile applications also reconfigure social, technological, and generic relations.